Safe Duration of Postoperative Monitoring for Malignant Hyperthermia Patients Administered Non-Triggering Anaesthesia: An Update. Issue 1 (January 2015) - Barnes, C.; Stowell, K. M.; Bulger, T.; Langton, E.; Pollock, N.
The postoperative care of malignant hyperthermia (MH) patients is subject to international variation, with a paucity of data in the literature to guide management. Over a series of three studies, our aim was to evaluate whether MH-susceptible patients (and relatives who had not yet been investigated), who had received a non-triggering anaesthetic, could be managed in the same way as the standard surgical population. Following a retrospective study, 206 anaesthetics were administered in a prospective second study to MH-susceptible/related individuals who were monitored for a minimum of one hour in the post anaesthesia care unit and a further 90 minutes in a step-down facility. No problems relating to MH were encountered. The postoperative monitoring time was subsequently changed and, in a third study, patients were managed no differently from standard surgical patients. One hundred and twenty-five anaesthetics were administered with no evidence of problems. This data shows that standard postoperative monitoring times are safe and appropriate in MH-susceptible patients.